Analisis Perbedaan Self-Disclosure di Media Sosial pada Remaja ditinjau Berdasarkan Pola Asuh - Susanti, Elda; Winata, Efan Yudha (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The study was aimed to analyze the disparity of self-disclosure of adolescence on social media viewed based on pattern of care. The study used quantitative approach with the type of study was comparative study. The sampling technique deployed in this study was purposive sampling technique, with the total samples were 351 samples. The research instrument consisted of two scales, they were self-disclosure scale and pattern of care scale. The result of the study showed that there was a significant difference between self-disclosure and pattern of care in adolescence. In the T-test calculation using Equal Variance Assumed (assuming the same variance, the analysis results were obtained with a significance value (Sig.) of 0.000, which means it is smaller than 0.05, so it can be concluded that Ha is accepted and Ho is rejected. Thus, it can be concluded that there is a difference in self-disclosure on social media in adolescents as viewed based on parenting patterns